Necroptotic kinases are involved in the reduction of depression-induced astrocytes and fluoxetine’s inhibitory effects on necroptotic kinases - Zeb, Salman; Ye, Huan; Liu, Yuan; Du, Hua-Ping; Guo, Yi; Zhu, Yong-Ming; Ni, Yong; Zhang, Hui-Ling; Xu, Yuan (Frontiers in Pharmacology, 2023)
The role of astrocytes in major depressive disorder has received great attention. Increasing evidence indicates that decreased astrocyte numbers in the hippocampus may be associated with depression, but the role of necroptosis in depression is unknown. Here, in a chronic unpredictable mild stress (CUMS) mouse model and a corticosterone (Cort)-induced human astrocyte injury model in vitro, we found that mice treated with chronic unpredictable mild stress for 3–5 weeks presented depressive-like behaviors and reduced body weight gain, accompanied by a reduction in astrocytes and a decrease in astrocytic brain-derived neurotropic factors (BDNF), by activation of necroptotic kinases, including RIPK1 (receptor-interacting protein kinase 1)/p-RIPK1, RIPK3 (receptor-interacting protein kinase 3)/p-RIPK3 and MLKL (mixed lineage kinase domain-like protein)/p-MLKL, and by upregulation of inflammatory cytokines in astrocytes of the mouse hippocampus. In contrast, necroptotic kinase inhibitors suppressed Cort-induced necroptotic kinase activation, reduced astrocytes, astrocytic necroptosis and dysfunction, and decreased Cort-mediated inflammatory cytokines in astrocytes. Treatment with fluoxetine (FLX) for 5 weeks improved chronic unpredictable mild stress-induced mouse depressive-like behaviors; simultaneously, fluoxetine inhibited depression-induced necroptotic kinase activation, reversed the reduction in astrocytes and astrocytic necroptosis and dysfunction, decreased inflammatory cytokines and upregulated brain-derived neurotropic factors and 5-HT1A levels. Furthermore, fluoxetine had no direct inhibitory effect on receptor-interacting protein kinase 1 phosphorylation. The combined administration of fluoxetine and necroptotic kinase inhibitors further reduced corticosterone-induced astrocyte injury. In conclusion, the reduction in astrocytes caused by depressive-like models in vivo and in vitro may be associated with the activation of necroptotic kinases and astrocytic necroptosis, and fluoxetine exerts an antidepressive effect by indirectly inhibiting receptor-interacting protein kinase 1-mediated astrocytic necroptosis.